Korelasi Diskursus al-Riwayah wa al-Diroyah dengan Al-Jarhu wa al-Ta'dil secara Global dalam Perspektif Sosiolinguistik - Abdurahim, Mika; Arifin, Tajul (Darul Yasin Al Sys, 2024)
This research aims to understand the relationship (correlation) of the hadith science Riwayah wa al-Diroyah with the branch of hadith science, Al-Jarhu wa al-Ta'dil globally, as well as how these two sciences are reflected in sociolinguistic aspects. This study analyzes the hadith science of al-Riwayah wa al-Diroyah and its relationship with the branch of hadith science Al-Jarhu wa al-Ta'dil, by paying attention to linguistic and sociological aspects from a sociolinguistic perspective. This research methodology uses qualitative methods with data collection techniques and literature study. The data used is primary data sourced from discussions about Riwayah wa Diroyah and Al-Jarhu wa Ta'dil which are exemplified in the field of ulumul hadith, and secondary data uses books, research reports, journal articles and other scientific papers. In fact, the hadith sciences Riwayah wa Diroyah and Al-Jarhu wa at-ta'dil are Islamic sciences that have existed since the time the Prophet Muhammad was still alive and are the core of Islamic scientific heritage to this day, while Al-Jarhu wa Ta'dil is a branch of science. hadith relating to the validity of the hadith narrator.